Simultaneous PET/Mri in Stroke: A Case Series. Issue 9 (September 2015) - Werner, Peter; Saur, Dorothee; Zeisig, Vilia; Ettrich, Barbara; Patt, Marianne; Sattler, Bernhard; Jochimsen, Thies; Lobsien, Donald; Meyer, Philipp M; Bergh, Florian Then; Dreyer, Antje; Boltze, Johannes; et al.
Prospective studies on magnetic resonance imaging (MRI)-guided systemic thrombolysis 44.5 hours after stroke onset did not reach their primary end points. It was discussed and observed in post hoc data re-assessment that this was partly because of limited MRI accuracy to measure critical hypoperfusion. We report the first cases of simultaneous [ 15 O]H2 O-positron emission tomography (PET)/MRI in stroke patients and an ovine model. Discrepancies between simultaneously obtained PET and MRI readouts were observed that might explain the above current limitations of stroke MRI. By offering highly complementary information, [ 15 O]H2 O-PET/MRI might help to identify critically hypoperfused tissue resulting in an improved patient stratification in thrombolysis trials.